(untitled) (The Peerian Journal, 2022)
The study of the formation and development of the patriotic spirit among our students has risen to the level of state policy. The future of a country and a nation is easy to predict, depending on the goals and aspirations of young people, their level of education, their understanding of their duties and responsibilities to the Motherland, people and nation. It is advisable to educate students in the spirit of high patriotism, to effectively use the pages of our centuries-old national and cultural heritage, values, history and traditions. The manifestation of patriotism reveals high noble aspirations, qualities of self-sacrifice for their people, their Motherland. The article argues that patriotism and humanity are complex and, of course, unprecedented phenomena.